Verbal Clauses in the Novel "Walana Fii Al-Halali Liqa'un" by Ahmad Atho Kenneth L. Pike's Tagmemic Perspective - Syu'ur, Santi Fajryanti; Fitriani, Laily (Maharaat: Jurnal Pendidikan Bahasa Arab, 2023)
This study aims to determine the forms of verbal clauses and their structures in the novel "Walanaa fii al-Halali Liqa'un" by Ahmad Atho based on Kenneth L. Pike's tagmemic perspective. This research is descriptive qualitative research. The main data source is taken from the novel "Walana fii al-Halali Liqa'un" by Ahmad Atho. Data collection techniques used three methods: translation techniques, reading techniques, and note-taking techniques. Data analysis techniques consist of data reduction, data presentation, and conclusion. The results of this study are that there are two types of verbal clauses in the novel "Walanaa fii al-Halali Liqa'un”, namely: (1) transitive clauses which are classified into four types, namely: (a) active transitive verbal clauses (fi'il ma'lum) has the structure musnad (M) + musnad ilaih (MI) + maf'ul bih (MB) + complement 1 + complement 2; (b) the passive transitive verbal clause (naibul fa'il) has an adverb structure adverb + fi'il (M) + naibul fail (NF); (c) the medial transitive verbal clause or reflection has the structure of musnad (M) + Musnad ilaih (MI) + maf'ul bih (MB) + complement; (d) the reciprocal transitive verbal clause has the structure musnad (M) + musnad ilaih (MI) + maf'ul bih (MB) + complement and (2) the intransitive verbal clause is no longer classified, has the structure musnad (M) + musnad ilaih ( MI) + complement.